“Hemorrhagic Transformation Following Thrombolytic Therapy in Acute Ischemic Stroke: A Case Series of 5 Patients” - Dave, Kinjal; Shrotriya, Ekta; Gupta, Sapna; Malhotra, Supriya (Nepal Journal of Neuroscience, 2023)
Stroke stands as a global health menace, causing substantial disability and mortality. Timely intervention, specifically within the critical "Golden Hour" following acute ischemic stroke, is imperative. Thrombolytic agents like tissue plasminogen activators (tPA) are pivotal for clot dissolution and blood flow restoration, yet their use introduces the risk of hemorrhagic transformation (HTF).In a recent case series involving five patients receiving thrombolytic therapy for acute ischemic stroke, we illuminate the occurrence of post-treatment HTF, its clinical ramifications, and the intricate challenges in its management. Early intervention in acute ischemic stroke aims to safeguard at-risk brain tissue, with thrombolytic therapy, notably tPA, serving as a primary treatment avenue. However, the associated risk of HTF hovers around 30%–35%, influenced by factors like age, comorbidities, and infarct size. The vulnerable ischemic penumbra, marked by a compromised blood-brain barrier and free radical generation, is particularly susceptible. Treatment decisions, guided by the National Institutes of Health Stroke Scale (NIHSS), pivot on stroke severity assessment, emphasizing the need for vigilant post-treatment monitoring. In conclusion, navigating the delicate balance between the benefits of early thrombolysis and the risks of HTF remains a persistent challenge in optimizing outcomes for acute ischemic stroke patients.